IMPLEMENTATION OF PRESIDENTIAL REGULATION NUMBER 13 OF 2018 CONCERNING THE APPLICATION OF THE PRINCIPLE OF RECOGNIZING CORPORATION BENEFICIAL OWNERS IN THE FRAMEWORK OF PREVENTION AND ERADICATION OF MONEY LAUNDERING AND TERRORISM FINANCING IN CONNECTION W - Andi Yudistira; Ratna Januarita; Yenni Yunithawati Rukmana (PT. Jurnal Center Indonesia Publisher, 2025)
Beneficial Owner or beneficial owner in Presidential Decree Number 13 of 2018, explained as holder power and authority the highest one has control full towards the Corporation as a GMS. Based on his rights as regulated​ in Presidential Decree Number 13 of 2018 , Beneficial Owners have​ equal standing​ with Major Shareholders who have shares , rights sound and get profit more of the 25% where has exceeding the ownership limit share holder share main namely at least 20% in the company . Corporations are often used as tool somebody For avoid not quite enough answer disclosure origin treasure riches as well as use assets . Misuse ownership benefit can harm holder share minorities , employees , creditors , and lead to crime businesses that are detrimental to the country, such as act criminal corruption , crime criminal money laundering , crime criminal funding terrorism , and others . The role of notaries in recognize Owner Sorry in Corporations , have obligation For to apply principle recognize Owner Benefits done through identification , verification and monitoring towards the Corporation as user service as regulated​ in Presidential Decree Number 13 of 2018 and Perkumham Number 15 of 2019. However , in reality matter the Not yet can implemented in a way maximum because of its complexity structure ownership in a Corporation and No existence clarity position about Beneficial Owner or beneficial owner in UUPT, apart from That Still many Corporations as user services that are still Not yet cooperative in give information related The Beneficial Owner is the real . Vacancy law related position Beneficial Owner or beneficial owner in a Corporation because Still Not yet there is arrangement legislation that regulates in a way clear and specific .